Accompanying Symptoms Overlap during Attacks in Menière’s Disease and Vestibular Migraine - Lopez-Escamez, Jose Antonio; Dlugaiczyk, Julia; Jacobs, Julien; Lempert, Thomas; Teggi, Roberto; von Brevern, Michael; Bisdorff, Alexandre (Frontiers in Neurology, 2014)
Meniere’s disease and vestibular migraine are the most common causes of spontaneous recurrent vertigo. The current diagnostic criteria for the two disorders are mainly based on patients’ symptoms and no biological marker is available. When applying these criteria, an overlap of the two disorders is occasionally observed in clinical practice. Therefore, the present prospective multi-center study aimed to identify accompanying symptoms that may help to differentiate between Meniere’s disease (MD), vestibular migraine (VM) and probable vestibular migraine (pVM). Two hundred and sixty-eight patients were included in the study (MD: n = 119, VM: n = 84, pVM: n = 65). Patients with MD suffered mainly from accompanying auditory symptoms (tinnitus, fullness of ear and hearing loss), while accompanying migraine symptoms (migraine-type headache, photo-/phonophobia, visual aura), anxiety and palpitations were more common during attacks of VM. However, it has to be noted that a subset of MD patients also experienced (migraine-type) headache during the attacks. On the other hand, some VM/pVM patients reported accompanying auditory symptoms. The female/male ratio was statistically higher in VM/pVM as compared to MD, while the age of onset was significantly lower in the former two. The frequency of migraine-type headache was significantly higher in VM as compared to both pVM and MD. Accompanying headache of any type was observed in declining order in VM, pVM and MD. In conclusion, the present study confirms a considerable overlap of symptoms in MD, VM and pVM. In particular, we could not identify any highly specific symptom for one of the three entities. It is rather the combination of symptoms that should guide diagnostic reasoning. The identification of common symptom patterns in VM and MD may help to refine future diagnostic criteria for the two disorders.